Fitness and Ecological Risk of Hybrid Progenies of Wild and Herbicide-Tolerant Soybeans With EPSPS Gene - Liu, Laipan; Zhang, Li; Fu, Jianmei; Shen, Wenjing; Fang, Zhixiang; Dai, Ying; Jia, Ruizong; Liu, Biao; Liang, Jingang (Frontiers in Plant Science, 2022)
Exogenous genes of transgenic crops are usually transferred to their wild type relatives through pollen-mediated gene flow, which may change the ecological fitness and ability to invade wild populations, resulting in the weeding of wild plants and other unpredictable environmental impacts. In this study, the F1 generation of herbicide-resistant soybeans and wild soybeans was obtained by artificial pollination, F2 generation seeds were obtained by self-crossing, and the fitness of the parents and their F1 and F2 generations was tested. The foreign protein EPSPS was expressed normally in the hybrid between transgenic and wild soybeans; however, the protein expression was significantly lower than that in transgenic soybeans. The fitness of the F1 hybrid between transgenic and wild soybeans was significantly lower than that of its parent. Compared with those of the wild soybeans, the F2 generation soybeans improved in some fitness indices, while the emergence rate, pollen germination rate, and number of full seeds per pod, pods per plant, and full seeds per plant did not significantly differ. The aboveground biomass and 100-seed weight of the F2 generation were higher than those of wild soybeans. Fitness among the F2 negative plants, homozygous, and heterozygous positive plants did not significantly vary. Improved fitness and presence of foreign genes in the F2 soybean were not significantly correlated. As the F2 generation of transgenic and wild soybeans had no fitness cost and the flowering stage were overlapped, the foreign gene might still spread in the wild soybean population.